Working with Words: Research Approaches to Translation-Oriented Lexicographic Practice - Tercedor, Maribel; López-Rodríguez, Clara; Faber, Pamela (TTR)

(untitled) (Association canadienne de traductologie, 2012)
Dictionaries ideally should address the needs of particular types of users. Their micro and macrostructural design should be oriented towards what user groups need to know about words and the uses that will be made of such knowledge. One specific use for dictionaries is the activity of translation. From the perspective of professional translators, dictionaries should allow for creativity and dynamicity in text production, providing solutions for changing communication needs. Dictionary-making for such a purpose can and should benefit from insights into words and meanings from other fields. Interdisciplinarity in Lexicography is just one example of how other fields interact in Translation Studies. In this paper we analyse how working in an interdisciplinary way is crucial to developing useful lexicographic and terminographic tools for translators and how methodologies, such as corpus-based work and experimental methods should be combined to offer converging evidence of different aspects of use and processing. We illustrate such work methods with examples from real lexicographic projects.